Pool segmentation for predicting water traps. (October 2015) - Yasui, Yusuke; McMains, Sara; Glau, Thomas
Abstract: We propose a new method to detect water trap regions in voids of oriented polygonal models that approximate the geometry of mechanical parts. Since water traps decrease cleaning and draining efficiency, accurately predicting such regions allows re-orienting parts to reduce manufacturing time and cost. We construct a directed graph that captures the flow of water in voids of a 3D input model, based on a fast orientation-dependent volume segmentation approach. We can quickly find the water trap regions by analyzing the directed graph. Since we take a purely geometric approach to solve this problem without employing any physical simulation, even if the geometry of the voids is complicated, we can calculate water traps quickly.